Recursos artísticos para el aprendizaje de las Ciencias Naturales de segundo grado de la Escuela de Educación Básica Particular Amauta, Loja 2023 - Pineda Solórzano, María Luisa (2023)
This thesis work called “the artistic resources for learning Natural Science”, has as a general objective to analyze artistic learning resources, by means of a didactic plan for the enhancing of the Natural Sciences learning in the second grade of the Amauta Private Primary School, located in Loja 2023. In order to reach this general objective, three specific objectives were developed: the first focused on identifying the most effective artistic learning resources for Natural Sciences learning, the second on designing a didactic approach based on artistic learning resources for the improvement of the learning of natural sciences, and the last objective was to determine the impact of the didactic approach based on artistic learning resources for the improvement of the Natural Sciences learning in second grade students. To develop this research, it was used a type of descriptive investigation, with a quantitative approach and quasi-experimental design. During the investigation process, the scientific, analytical, synthetic, inductive, deductive, statistical and hermeneutic methods were applied. The instruments used were a structured and a pre- and post-evaluation questionnaire. These instruments contributed significantly to the data collection. The research population was the "Amauta" school from which, through a non-probabilistic sampling 12 students and a teacher were selected. It is important to mention that the research results indicate that the main artistic resources contribute significantly to enhancing the different Natural Sciences learning, this was evidenced by the application of the didactic approach, where artistic resources helped students to develop a deeper and more meaningful understanding of the concepts and phenomena addressed in Natural Sciences. The obtained results indicate that the integration of artistic resources in the teaching-learning process of these subjects, not only drew the students’ interest and attention, but also promoted a more dynamic and participatory learning atmosphere in students. Key words: teaching – learning, didactic resources, Natural Science, didactic approach.